Reorientation of Indonesia's Fiscal Policy: Analysis of Finance Minister Purbaya's Policy from an Islamic Economic Perspective - Muhammad Syafi'i (Jurnal Hukum Ekonomi Syariah, 2025)
This study examines fiscal policies during the early tenure of Finance Minister Purbaya through the lens of Islamic economic philosophy, focusing on three foundational principles: justice (al-‘adl), public benefit (al-maslahah), and trustworthiness (al-amānah). Using a qualitative-descriptive and comparative analytical approach, the study evaluates the government’s liquidity placement in state-owned banks (Himbara), the 8+4+5 stimulus package, and taxation policies. These evaluations are conducted through a series of analytical matrices, comparative tables, flow diagrams, benefit-distribution graphs, and an integrative conceptual model. The findings indicate unequal distribution of fiscal benefits, with corporations receiving the largest share, while micro, small, and medium enterprises (MSMEs), informal workers, and low-income households receive relatively fewer benefits. The strongest maslahah effects arise from food assistance and labor-intensive programs that directly address basic public needs, whereas bank liquidity policies generate only sectoral and complementary benefits. In terms of amānah, fiscal governance demonstrates transparency and administrative efficiency; however, reliance on conventional interest-based instruments and the regressive nature of VAT raise ethical concerns. Overall, the study concludes that Purbaya’s fiscal policies are partially aligned with Islamic economic values: some policies are consistent, some deviate, and others require reformulation to better serve vulnerable groups and adhere more closely to Sharia-compliant principles.